Carbon Capture, Storage and Utilisation Technologies - Awadh, Khaleel; Breaux, Vaughan; Arbeed, Bader Al (Carbon Capture, Storage and Utilisation Technologies, Edition 1, 2024)
This study is a review of current and future applications of methods of carbon capture and storage (CCS) and the bioconversion processes which aims to address the issue and cover various CCS technologies and their efficacy in reducing carbon emissions. A qualitative analysis of published papers is employed throughout to address the objectives. The results of this study show that, currently, oxyfuel, pre-combustion, and post-combustion technologies are most prevalent in the field of carbon capture implementation. The possibility of retrofitting the aforementioned technologies to existing plants and the subsequent benefits and drawbacks are discussed. The implementation of CCS has been observed most notably in the cement industry and in industries where carbon emissions are significant (e.g., refineries). Moreover, a number of new promising CCS technologies are described and discussed concurrently with their prospects for future developments (e.g., fuel cells, membranes, and chemical looping). Specific case studies of organizations involved in CCS have enabled comparisons to be drawn in relation to the financial costs and practicality of implementation. It has been noted that countries must offer incentives and assistance to organizations in order to motivate them to adopt CCS technologies. Additionally, sufficient conditions which are favourable to investors must be met in order to make venturing into carbon capture appealing and sustainable for them. The government may achieve this by legally imposing quotas on carbon emissions from specific industries, which creates an environment in which the CCS technologies become lucrative. It is suggested that it is important to explore the development of advanced plant designs that incorporate integration concepts and CCS technologies. For example, Shell has been exemplified as the leader of technological advancements in CCS and for the company’s venture into developing CCS for refineries. Public awareness is also an important aspect of ensuring the future of CCS technologies and projects. If people are well informed regarding the environmental and health impacts of carbon emissions, they are more likely to support and convince the government to adopt CCS technologies.